PENGARUH PENGGUNAAN BAHASA INDONESIA TERHADAP KEPUASAN PENGGUNA PORTAL LAYANAN MAHASISWA FASILKOM UPN “VETERAN” JATIM - Sholihatin, Endang; Ramadhan, Raihan; Jovian, Abraham Danar; Gabriel, Paskalis Reynaldy Elroy; Triwinanda, Rizqullah Sandya Yossie; Ramadhani, Muhammad Nabil; Bimantoro, Ryan Bagus (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2023)
This study discusses the influence of the Indonesian language on user satisfaction in the development and use of student service portals at the Faculty of Computer Science at the National Development University